How to Make Determinants of Capital Structure in the Cement Sector of Pakistan from Educational Perspective - Swera Sharf (Universitas Pendidikan Indonesia (UPI), 2023)
Capital structure, which in finance states to the ratio of liability to equity, illustrates how the company finances their total operations and how organizational growth requires various sources of funding. In this study, researchers suggested determining the variables that have the maximum impact on capital structure in the Pakistan cement industry, which is recorded on the Karachi Stock Exchange. Growth rate, profitability, tangibility, and business size were acknowledged by the researchers as factors that have an impact on leverage. To gather data, the researchers used a balance sheet study published by the State Bank (SBP) on a sample of 6 major companies out of a total of 21, and they used regression, correlation, and ANOVA to examine the factors influencing capital structuring in the cement industry from 2013 to 2017. The results showed that other than earning, which takes a negative association with leverage in business, all criteria listed have a favorable impact on leverage. The firm will be able to assess its capital structure needs to be based on debts and equity with the use of this research. Additionally, it will enhance students, researchers, and managers' knowledge of capital structuring.